2016
DOI: 10.1039/c5nr06534h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning photoluminescence and surface properties of carbon nanodots for chemical sensing

Abstract: Obtaining tunable photoluminescence (PL) with improved emission properties is crucial for successfully implementing fluorescent carbon nanodots (fCDs) in all practical applications such as multicolour imaging and multiplexed detection by a single excitation wavelength. In this study, we report a facile hydrothermal approach to adjust the PL peaks of fCDs from blue, green to orange by controlling the surface passivation reaction during the synthesis. This is achieved by tuning the passivating reagents in a step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Zhang et al. reported the synthesis of the green, blue, and orange emission of CDs through the sequential passivation with PEG1000 and 2,2′‐(ethylenedioxy)bis(ethylamine), which resulted from the different oxygen states and N configurations (Figure b) . As shown in the above examples, surface passivation plays an important role in controlling the surface state of CDs without altering the core states of the CDs.…”
Section: Optical Propertiesmentioning
confidence: 97%
“…Zhang et al. reported the synthesis of the green, blue, and orange emission of CDs through the sequential passivation with PEG1000 and 2,2′‐(ethylenedioxy)bis(ethylamine), which resulted from the different oxygen states and N configurations (Figure b) . As shown in the above examples, surface passivation plays an important role in controlling the surface state of CDs without altering the core states of the CDs.…”
Section: Optical Propertiesmentioning
confidence: 97%
“…The F 0 /F‐1 ratio had an obviously very relating linear ( R 2 = 0.9976) with the Fe 3+ concentration in the range from 0 to 200 × 10 −6 m in Figure 7c, compared with the previously reported values, it was much larger. [ 41,42 ] Herein, F and F 0 were the fluorescence intensities of the WBPU‐3 film at 420 nm in the presence and absence of Fe 3+ ions, respectively. The limit of detection (LOD) was evaluated to be 2.19 × 10 −6 m at a signal‐to‐noise ratio of 3.…”
Section: Resultsmentioning
confidence: 99%
“…[134] Hence, surface modification is another route to achieve multicolor and long wavelength emissions in CDs. [144] In their report, PEG 400 was first heated up in a round-bottom flask at 150°C for 12 h until a faint yellow solution was formed. [143] Detailed studies were carried out to investigate the surface states and it was found that surface moieties such as C═O and C═N were found on multicolor CDs, which could introduce a lot of structural configurations and new energy levels, resulting in many electronic transition possibilities.…”
Section: Luminescence Properties and Synthesismentioning
confidence: 99%